Classification of preganglionic neurones projecting into the cat cervical sympathetic trunk. - Boczek-Funcke, Ansgar; Dembowsky, Klaus; Häbler, Heinz-Joachim; Jänig, Wilfrid; McAllen, R. M.; Michaelis, M. (The journal of physiology, 1992)
1. The spontaneous and reflex activity patterns of 167 single preganglionic axons dissected from the cervical sympathetic trunk were examined in chloralose-anaesthetized cats. Each neurone was classified into one of four major groups, on the basis of three principal criteria: the presence or absence of significant cardiac rhythmicity of the activity, the response to noxious stimulation of the skin, and the coupling of its activity to central inspiratory drive (phrenic nerve activity). Most neurones were also subjected to additional tests, which included carotid chemoreceptor stimulation, nasopharyngeal probing, systemic hypercapnia (ventilation with 8% CO2), hyperventilation, adrenaline-induced blood pressure rises and retinal illumination. 2. Group I neurones (n = 69; 41%) showed significant cardiac rhythmicity, indicating strong baroreceptor control. Most (54/69) were excited by noxious stimuli, the rest being unaffected. Their activity showed variable degrees of excitatory coupling to the central inspiratory drive, and was enhanced by hypercapnia (35/39). Their responses to stimulation of arterial chemoreceptors (12/15) and nasopharyngeal receptors (24/35) were excitatory. 3. Group II neurones (n = 39; 23%) were inhibited by noxious stimulation of skin. With nine exceptions, they showed no significant cardiac rhythmicity, although they were weakly inhibited by an adrenaline-induced blood pressure rise. Their coupling to central inspiratory drive was weak or absent, and their responses to hypercapnia and hyperventilation were variable. By contrast to other groups, they were inhibited by both chemoreceptor stimulation (9/10) and nasopharyngeal stimulation (17/18). 4. Group III neurones (n = 33; 20%) showed no significant cardiac rhythmicity, but their activity was closely coupled to central inspiratory drive. They were inhibited by hyperventilation (9/9) and excited by hypercapnia (20/21), but only fired during the central inspiratory phase and sometimes during late expiration. Their responses to noxious stimulation (28/33), chemoreceptor stimulation (8/11) and nasopharyngeal probing (24/24) were excitatory, but the induced activity was ‘gated’ by the respiratory cycle, occurring primarily during inspiration and avoiding the postinspiratory phase. 5. Group IV neurones (n = 26; 16%) showed no significant cardiac or respiratory related activity and were either excited (n = 22) or unaffected (n = 4) by noxious stimuli. One of the latter and three group II neurones were inhibited by retinal illumination; thirty-one other neurones of all classes were unaffected. 6. Approximately 45% of thoracic sympathetic neurones were silent under the experimental conditions. About 25% of these could be recruited by systemic hypercapnia leaving 34% without spontaneous and reflex activity.(ABSTRACT TRUNCATED AT 400 WORDS)
Gesehen am 22.10.2024